1999
DOI: 10.1093/rheumatology/38.7.668
|View full text |Cite
|
Sign up to set email alerts
|

Extra-articular rheumatoid arthritis: prevalence and mortality

Abstract: In this series, serositis and cutaneous vasculitis were predominant extra-articular manifestations of RA; and mortality was greater in the ExRA than in the non-ExRA subgroup, perhaps due to a high frequency of associated heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
179
0
19

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 225 publications
(206 citation statements)
references
References 5 publications
8
179
0
19
Order By: Relevance
“…In this same cohort of patients, previous studies have shown the 30-year cumulative incidence of any extraarticular disease manifestation to be 46.0% and that of severe extraarticular disease to be 16.7% (13,14). The presence of severe extraarticular RA was a predictor of all noncardiac vascular disease subtypes, except for cerebrovascular disease alone.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…In this same cohort of patients, previous studies have shown the 30-year cumulative incidence of any extraarticular disease manifestation to be 46.0% and that of severe extraarticular disease to be 16.7% (13,14). The presence of severe extraarticular RA was a predictor of all noncardiac vascular disease subtypes, except for cerebrovascular disease alone.…”
Section: Discussionmentioning
confidence: 54%
“…Patients with RA, and particularly those with extraarticular RA, have an increased mortality due to cardiovascular disease (3,8,14,22). In patients with severe extraarticular RA, an increased mortality specifically due to heart disease has been suggested (14), and data from studies of larger patient samples indicate an increased mortality (27) and morbidity (28) from cardiovascular disease in this subset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations